The effects of solid state fermented common vetch ( Vicia sativa) with Aspergillus niger in broilers - Işik, Ö; Kırkpınar, F (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, the effects of 20% raw vetch, solid state fermented vetch and enzyme added raw vetch addition in broiler diets on performance, carcass characteristics, meat quality and digestibilty were investigated. Aspergillus niger was used as a microorganism in the solid state fermentation of raw vetch seeds and fermentation continued for 72 hours. According to the findings obtained during the experiment period lasting forty-two days; the fermentation process had no significant effect on the performance parameters for the entire production period compared to the use of raw vetch. When vetch was used as raw, fermented or enzyme addition, there was a tendency to increase the live weight of the groups. The use of vetch had a positive effect on breast meat weights and yields. Fermentation or enzyme addition to raw vetch did not affect the carcass parameters. The relative duedonum weight decrease with fermentation or using enzyme, also jejunum+ileum relative weights. While the L* value of breast meat increased in the enzyme added raw vetch group addition, the a* value decreased in the fermented vetch and enzyme added raw vetch groups, and the breast meat a* value and but L*, a* and b* values did not change. pH, nutrient values, breast meat thawing-cooking losses, water holding capacity and sensory analysis values in breast and tight meats were not affected by the treatments. Digestibilty of feeds did not affected in all treatments. According to these results, considering that there is an increasing trend in live weights, it may be recommended to use vetch at the level of 20% raw, fermented or enzyme addition in broiler diets.